Homevoters vs. Leasevoters: A Spatial Analysis of Airport Effects - Gabriel Ahlfeldt; Wolfgang Maennig (Center for Economic Studies and ifo Institute (CESifo), 2013)
We use a public referendum on a new air traffic concept in Berlin, Germany as a natural experiment to analyze how the interaction of tenure and capitalization effects shapes the outcome of direct democracy processes. We distinguish between homevoters, i.e., voters who are homeowners, and leasevoters, i.e., voters who lease their homes. We expect homevoters to be more likely to support or oppose initiatives that positively or negatively affect the amenity value of a neighborhood because some of the related benefits or costs of leasevoters are neutralized by adjustments in market rents (capitalization). Our empirical results are in line with our theoretical expectations and imply that public votes on local public goods do not necessarily reflect the spatial distribution of welfare effects in mixed-tenure environments.
Keywords: D61; D62; H41; H71; L83; I18; R41; R58; 330; referendum; homevoters; leasevoters; NIMBYism; rents; noise; airports; Berlin